PRODUCTION AND INCOME ANALYSIS OF DRIED FISH BUSINESS IN BENGKULU CITY - Bambang Sumantri; Irnad; Winta Septria; Melly Suryanti; Widya Kartika Laksmawati (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2023)
The research objective was to analyze the factors that influence the dried fish business and the dried fish business income in Bengkulu City. The research was conducted in Kampung Melayu District, Bengkulu City. The research population is salted and fresh dried fish. The total respondents respectively are 65 and 56 people. The analytical method used is the Cobb-Douglas production function model to answer the first objective and income analysis to answer the second objective. The results of the study concluded: (1) the results of the F test analysis of the business of making salted and fresh dried fish had a significant effect on the variable production of salted and fresh dried fish. The results of the T-test on the production model of the business of making salted dried fish have three influential factors, namely Raw Materials (BB), Labor (TK), and Dummy (D). The dry fish production model only has one factor that has a significant effect, namely Raw Materials (BB). (2) Based on the results of the analysis, the costs incurred for the production of salted dried fish are IDR 2,874,932/week and the costs incurred for the production of fresh dried fish are IDR2,392,144/week. Revenue for salted dried fish makers are IDR6,116,308/week and for fresh dried fish makers are IDR4,557,411/week. The income of the salt dried fish maker are IDR3,241,375/week and the fresh dried fish maker are IDR2,185,266/week. R/C Ratio analysis obtained efficiency values of 2.13 and 1.91 respectively so the business is carried out proved to be efficient.